Beyond the Antigen Receptor: Editing the Genome of T-Cells for Cancer Adoptive Cellular Therapies - Lloyd, Angharad; Vickery, Owen N.; Laugel, Bruno (Frontiers in Immunology, 2013)
Recent early-stage clinical trials evaluating the adoptive transfer of patient CD8+ T-cells re-directed with antigen receptors recognising tumours have shown very encouraging results. These reports provide strong support for further development of the therapeutic concept as a curative cancer treatment. In this respect combining the adoptive transfer of tumour-specific T-cells with therapies that increase their anti-tumour capacity is viewed as a promising strategy to improve treatment outcome. The ex-vivo genetic engineering step that underlies T-cell re-direction offers a unique angle to combine antigen receptor delivery with the targeting of cell intrinsic pathways that restrict T-cell effector functions. Recent progress in genome editing technologies such as protein- and RNA-guided endonucleases raise the possibility of disrupting gene expression in T-cells in order to enhance effector functions or to bypass tumour immune suppression. This approach would avoid the systemic administration of compounds that disrupt immune homeostasis, potentially avoiding autoimmune adverse effects, and could improve the efficacy of T-cell based adoptive therapies.